Specific features of management of IT-consulters innovative projects - T. V. Kakatunova; E. I. Ivanova (Путеводитель предпринимателя, 2020)
Authors shows the way of how to manage innovation projects in IT-development and consulting. In article the method of compilation and controlling portfolios of innovative projects as the part of enterprise management toolkit is given.